2020
DOI: 10.3389/fphy.2020.568243
|View full text |Cite
|
Sign up to set email alerts
|

A High-Granularity Digital Tracking Calorimeter Optimized for Proton CT

Abstract: A typical proton CT (pCT) detector comprises a tracking system, used to measure the proton position before and after the imaged object, and an energy/range detector to measure the residual proton range after crossing the object. The Bergen pCT collaboration was established to design and build a prototype pCT scanner with a high granularity digital tracking calorimeter used as both tracking and energy/range detector. In this work the conceptual design and the layout of the mechanical and electronics implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Subsequent design optimization and experimental measurements (Pettersen et al 2019a, Tambave et al 2019 showed promise in regards to proton imaging, as well as detection of heavier ions. The DTC is currently under development and prototyping (Alme et al 2020).…”
Section: Helium Imagingmentioning
confidence: 99%
“…Subsequent design optimization and experimental measurements (Pettersen et al 2019a, Tambave et al 2019 showed promise in regards to proton imaging, as well as detection of heavier ions. The DTC is currently under development and prototyping (Alme et al 2020).…”
Section: Helium Imagingmentioning
confidence: 99%
“…Possible input variables of known uncertainty are the detector output or reconstructed proton paths. All steps in the pipeline from this input to the output must be differentiated in order to apply (6). Thus derivatives of GATE are not required in any case.…”
Section: Quantification Of Uncertaintymentioning
confidence: 99%
“…37 Figure 11a shows one column of its Jacobian matrix, i. e. the change of the reconstructed image if one sensor pixel changes. We used the Jacobian matrix according to (6) to propagate uncertainties in the sinogram x through the FBP algorithm to the reconstructed image y, and visualized it in figure 11b with the level-crossing probability colouring that indicates the likelihood of each voxel to be on the wrong side of the isocontour. 53 Note that all these results can be produced without AD because the FBP is a linear map.…”
Section: Derivatives Of the Filtered Back-projection Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton CT scanner prototypes proposed and developed so far rely either on a calorimeter, e.g. a scintillator, to measure the energy deposited by a proton therein (Civinini et al, 2013;Johnson et al, 2016;DeJongh et al, 2021) or a range telescope (Taylor et al, 2016;Alme et al, 2020;Pemler et al, 1999). An alternative measurement principle determines the proton's time of flight (TOF) between two or more sensor planes from which the velocity and thus the kinetic energy can be calculated.…”
Section: Introductionmentioning
confidence: 99%